2015
DOI: 10.3390/en8053720
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Electric Vehicles and Their Used Batteries for Peak-Load Shifting

Abstract: Abstract:The utilization of electric vehicles (EV) and their used batteries in supporting small-scale energy management systems were studied. Both theoretical study and practical demonstration were performed to measure the feasibility of the developed system. Each five EVs and used EV batteries were used along with 20 kW photovoltaic (PV) panels as a renewable energy source. The main objective of the developed system is performing a peak-load shifting by utilizing EVs, used EV batteries and PV panels. The plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 22 publications
0
79
0
Order By: Relevance
“…Both battery electric vehicles (BEVs) and plug-in hybrid electric vehicle loads (PHEVs) have been presented by considering the effect on vehicle-to-grid. (V2G) and grid-to-vehicle (G2V) power curves in terms of power demand [5]. The different level of penetration of BEVs and EVs will be directly impacted by the power demand response.…”
Section: Introductionmentioning
confidence: 99%
“…Both battery electric vehicles (BEVs) and plug-in hybrid electric vehicle loads (PHEVs) have been presented by considering the effect on vehicle-to-grid. (V2G) and grid-to-vehicle (G2V) power curves in terms of power demand [5]. The different level of penetration of BEVs and EVs will be directly impacted by the power demand response.…”
Section: Introductionmentioning
confidence: 99%
“…Locment et al [19] presented an evaluation on PV micro-grid power architecture for efficient charging of plug-in EVs from the aspects of theoretical and numerical. Aziz's [20] studies showed that the application of EVs and used EV batteries in supporting certain small-scale energy management systems is feasible. From this perspective, storage facilities must be provided to reduce the possibility of abandoned electricity given that EVs can provide storage capacity [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development and use of electric vehicles (EVs) are widely considered as one of the solutions for energy-saving and emission-reduction in the world [1][2][3]. With the large-scale adoption of EVs on expressways, building fast-charging stations (CSs) (with CS planning technology [4]) will be necessary for people to drive the cars for a long distance.…”
Section: Introductionmentioning
confidence: 99%